2019
DOI: 10.1101/787606
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Maximizing Dissimilarity in Resting State detects Heterogeneous Subtypes in Healthy population associated with High Substance-Use and Problems in Antisocial Personality

Abstract: Patterns in resting-state fMRI (rs-fMRI) are widely used to characterize the trait effects of brain function. In this aspect, multiple rs-fMRI scans from single subjects can provide interesting clues about the rs-fMRI patterns, though scan-to-scan variability pose challenges. Therefore, rs-fMRI's are either concatenated or the functional connectivity is averaged. This leads to loss of information. Here, we use an alternative way to extract the rs-fMRI features that are common across all the scans by applying C… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…Second, all participants were males, and the effects of MA on sex cannot be assessed. Finally, Kashyap, Bhattacharjee, Yeo, and Chen (2020) have shown that the general categorization of subjects based only on external symptoms (e.g., healthy vs. diseased, control vs. patient) should also consider aspects of a healthy subject's lifestyle habits and psyche. We did not select the control group from open datasets, which would bring some bias to the results (Kashyap et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Second, all participants were males, and the effects of MA on sex cannot be assessed. Finally, Kashyap, Bhattacharjee, Yeo, and Chen (2020) have shown that the general categorization of subjects based only on external symptoms (e.g., healthy vs. diseased, control vs. patient) should also consider aspects of a healthy subject's lifestyle habits and psyche. We did not select the control group from open datasets, which would bring some bias to the results (Kashyap et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Supporting the behavioural finding with neural markers, such as electroenchaphalography (EEG), functional near-infrared spectroscopy (fNIRS) , or functional magnetic resonance imaging (fMRI) could have validated the claim that whether a pathway is maximally utilized or not. A detailed analysis by constructing brain networks using data from multiple modalities can further aid our understanding of the mechanism of action of tDCS (Lauro et al, 2014;Sehatpour et al, 2020;Vecchio et al, 2021;Wang et al, 2020;Kashyap et al, 2016Kashyap et al, , 2019aKashyap et al, ,b, 2020Kashyap et al, , 2021b.…”
Section: Limitations Of the Thesismentioning
confidence: 99%